Open : the philosophy and practices that are revolutionizing education and science - Jhangiani, Rajiv; Biswas-Diener, Robert (Ubiquity Press, 2017)
"Affordable education. Transparent science. Accessible scholarship. These ideals are slowly becoming a reality thanks to the open education, open science, and open access movements. Running separate--if parallel--courses, they all share a philosophy of equity, progress, and justice. This book shares the stories, motives, insights, and practical tips from global leaders in the open movement."--Provided by publisher